Assessing China's carbon intensity pledge for 2020: Stringency and credibility issues and their implications - ZhongXiang Zhang (Fondazione Eni Enrico Mattei (FEEM), 2010)
Just prior to the Copenhagen climate summit, China pledged to cut its carbon intensity by 40-45% by 2020 relative to its 2005 levels to help to reach an international climate change agreement at Copenhagen or beyond. This raises the issue of whether such a pledge is ambitious or just represents business as usual. To put China's climate pledge into perspective, this paper examines whether this proposed carbon intensity goal for 2020 is as challenging as the energy-saving goals set in the current 11th five-year economic blueprint, to what extent it drives China's emissions below its projected baseline levels, and whether China will fulfill its part of a coordinated global commitment to stabilize the concentration of greenhouse gas emissions in the atmosphere at the desirable level. Given that China's pledge is in the form of carbon intensity, the paper shows that GDP figures are even more crucial to the impacts on the energy or carbon intensity than are energy consumption and emissions data by examining the revisions of China's GDP figures and energy consumption in recent years. Moreover, the paper emphasizes that China's proposed carbon intensity target not only needs to be seen as ambitious, but more importantly it needs to be credible. Finally, it is concluded with a suggestion that international climate change negotiations need to focus on 2030 as the targeted date to cap the greenhouse gas emissions of the world's two largest emitters in a legally binding global agreement.
Keywords: Q42; Q43; Q48; Q52; Q53; Q54; Q58; 330; Carbon Intensity; Post-Copenhagen Climate Change Negotiations; Climate Commitments; China